Regulation of Schwann cell proliferation and migration via miR-195-5p-induced Crebl2 downregulation upon peripheral nerve damage - Li, Shiying; Wu, Wenshuang; Zhang, Jing; Chen, Yu; Wu, Yumeng; Wang, Xinghui (Frontiers in Cellular Neuroscience, 2023)
Background Schwann cells acquire a repair phenotype upon peripheral nerve injury (PNI), generating an optimal microenvironment that drives nerve repair. Multiple microRNAs (miRNAs) show differential expression in the damaged peripheral nerve, with critical regulatory functions in Schwann cell features. This study examined the time-dependent expression of miR-195-5p following PNI and demonstrated a marked dysregulation of miR-195-5p in the damaged sciatic nerve. Methods CCK-8 and EdU assays were used to evaluate the effect of miR-195-5 on Schwann cell viability and proliferation. Schwann cell migration was tested using Transwell and wound healing assays. The miR-195-5p agomir injection experiment was used to evaluate the function of miR-195-5p in vivo. The potential regulators and effects of miR-195-5p were identified through bioinformatics evaluation. The relationship between miR-195-5p and its target was tested using double fluorescence reporter gene analysis. Results In Schwann cells, high levels of miR-195-5p decreased viability and proliferation, while suppressed levels had the opposite effects. However, elevated miR-195-5p promoted Schwann cell migration determined by the Transwell and wound healing assays. In vivo injection of miR-195-5p agomir into rat sciatic nerves promote axon elongation after peripheral nerve injury by affecting Schwann cell distribution and myelin preservation. Bioinformatic assessment further revealed potential regulators and effectors for miR-195-5p, which were utilized to build a miR-195-5p-centered competing endogenous RNA network. Furthermore, miR-195-5p directly targeted cAMP response element binding protein-like 2 (Crebl2) mRNA via its 3′-untranslated region (3′-UTR) and downregulated Crebl2. Mechanistically, miR-195-5p modulated Schwann cell functions by repressing Crebl2. Conclusion The above findings suggested a vital role for miR-195-5p/Crebl2 in the regulation of Schwann cell phenotype after sciatic nerve damage, which may contribute to peripheral nerve regeneration.